En sang til (livs)motet - en undring omkring fenomenet livsmot - Thorsen, Rolf (Nordisk tidsskrift for helseforskning, 2019)
Reflections on life courageThis essay addresses various aspects of the phenomenon of “life courage”. The approach is phenomenological and draws on a Danish tradition of life philosophy. The aim is not to find definitions, but to approach the topic cautiously to reveal new aspects of the phenomenon. The text is an outer and inner journey through experience, art, literature and poetry. This journey starts by dwelling on the apparent absence of courage for life in situations of extreme darkness. Later in the essay, light gradually appears, accompanied by increased life courage.